#### Answer

$x = -3$

#### Work Step by Step

$x^3 + 27 = 0$
$x^3 + 27 - 27 = -27 $
$x ^3 = -27 $
$\sqrt[3] {x^3} = \sqrt[3] {-27}$
$x = -3$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$x = -3$

$x^3 + 27 = 0$
$x^3 + 27 - 27 = -27 $
$x ^3 = -27 $
$\sqrt[3] {x^3} = \sqrt[3] {-27}$
$x = -3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.